2020
DOI: 10.1111/iej.13389
|View full text |Cite
|
Sign up to set email alerts
|

Microbial ecology and predicted metabolic pathways in various oral environments from patients with acute endodontic infections

Abstract: Aim To assess in a cross‐sectional clinical study the effect of antibiotics on the diversity, structure and metabolic pathways of bacterial communities in various oral environments in patients with acute primary infections. Methodology Samples of saliva (SA), supragingival biofilm (SB) and from the pulp cavity (PC) were collected from teeth with acute primary infections and then grouped according to previous use of antibiotics (NoAtb = no antibiotics [n = 6]; Atb = antibiotics [n = 6]). DNA sequencing was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Antibiotics not only affect the composition and functions of the oral microbiome, but also induce specific metabolic changes during antibiotic interventions (Moraes et al, 2020). Like previous studies (Monroy-Pérez et al, 2020), a prospective cohort study found that Shannon's diversity index was reduced by treatment with amoxicillin relative to that in the untreated group, and decreased continuously for 6 months (Menon et al, 2019).…”
Section: Antibiotic Utilizationmentioning
confidence: 71%
“…Antibiotics not only affect the composition and functions of the oral microbiome, but also induce specific metabolic changes during antibiotic interventions (Moraes et al, 2020). Like previous studies (Monroy-Pérez et al, 2020), a prospective cohort study found that Shannon's diversity index was reduced by treatment with amoxicillin relative to that in the untreated group, and decreased continuously for 6 months (Menon et al, 2019).…”
Section: Antibiotic Utilizationmentioning
confidence: 71%
“…This change results in a higher number of S. Mutans in the oral cavity. 48 In our study, the effect of insulin resistance on oral flora can be thus explained.…”
Section: Discussionmentioning
confidence: 76%
“…51 An increase in the S. Mutans count is detected in the oral microflora when saliva flow rate decreases. 48 In our study, the effect of PCOS on the oral flora can be explained based on these reasons.…”
Section: Discussionmentioning
confidence: 77%
“…Prospective cohort studies revealed that Shannon biodiversity index was decreased during amoxicillin treatment and was subject to further reduction in the following 6 months’ time period ( Menon et al, 2019 ; Monroy-Pérez et al, 2020 ; Nel Van Zyl et al, 2022 ). The density of Neisseria, Streptococcus and Veillonella strains in the oral cavity was also reported to decrease during treatment with amoxicillin ( Larsson Wexell et al, 2016 ; Moraes et al, 2020 ). Save commonly used amoxicillin, other groups of antibiotics with various mechanisms of action can influence the oral microbiota and promote the selection of multi-drug resistant strains and their horizontal transmission ( Zaura et al, 2015 ; Moraes et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The density of Neisseria, Streptococcus and Veillonella strains in the oral cavity was also reported to decrease during treatment with amoxicillin ( Larsson Wexell et al, 2016 ; Moraes et al, 2020 ). Save commonly used amoxicillin, other groups of antibiotics with various mechanisms of action can influence the oral microbiota and promote the selection of multi-drug resistant strains and their horizontal transmission ( Zaura et al, 2015 ; Moraes et al, 2020 ). Other factors that can lead to oral dysbiosis include: local and systemic diseases, improper oral hygiene, unbalanced diet, smoking tobacco and immunosuppression ( Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%